Hypervalent silicate-assisted azidation approach for the substituted azepane motif. (21st December 2022) - Sameem, Bilqees; Karuso, Peter; Liu, Fei
Graphical abstract: Abstract: An efficient and stereospecific azidation of a cis -disubstituted azepane is described as the first example of hypervalent silicate-assisted nucleophilic azidation on a substituted seven-membered azepane ring. DFT calculations suggest an SN 2-like mechanism whereby the azido nucleophile coordinated to the hypervalent silicate presents flexible geometries for the nucleophilic approach. The method provides a viable alternative to the classical Mitsunobu-based approaches in substituted seven-membered N -heterocycles with complex conformational properties.